2001
DOI: 10.1111/j.1651-2227.2001.tb01590.x
|View full text |Cite
|
Sign up to set email alerts
|

Successful treatment of refractory ascites in a child with transjugular intrahepatic portosystemic shunt

Abstract: A 16‐y‐old boy who had undergone bone marrow transplantation for relapsed acute lymphoblastic leukaemia developed liver cirrhosis and refractory ascites, which did not respond to salt restriction, diuretics and abdominal paracentesis. Liver transplantation was not feasible because of poor nutritional status, pre‐existing renal dysfunction and uncertainty about the prognosis of his leukaemia. The patient underwent a successful transjugular intrahepatic portosystemic shunt (TIPS), with immediate resolution of as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 11 publications
1
1
0
Order By: Relevance
“…This is in keeping with the previous report by Di Giorgio et al (15) and the standards for adult practice (6). This study has confirmed that a successful TIPSS is highly effective at controlling variceal bleeding and refractory ascites in children with resistant PHTN, as previously described (24,25). Furthermore, this study supports the report by Steventon et al that TIPSS may be used to control active haemorrhage and enable children to be listed and undergo successful liver transplantation (19).…”
Section: Discussionsupporting
confidence: 92%
“…This is in keeping with the previous report by Di Giorgio et al (15) and the standards for adult practice (6). This study has confirmed that a successful TIPSS is highly effective at controlling variceal bleeding and refractory ascites in children with resistant PHTN, as previously described (24,25). Furthermore, this study supports the report by Steventon et al that TIPSS may be used to control active haemorrhage and enable children to be listed and undergo successful liver transplantation (19).…”
Section: Discussionsupporting
confidence: 92%
“…Since the first study in 1982, transjugular intrahepatic portosystemic shunts (TIPS) have been widely used to control portal hypertension and its complications 1 . Although more than 2000 TIPS procedures in adults have been published, paediatric experience is limited to case reports and small series 2–8 . The technical success rate in paediatric patients, ranging from 75 to 90%, 9 is lower than in adults (95%) 10 .…”
Section: Introductionmentioning
confidence: 99%